A6_8 Supermassive Black Holes Merger: Violation of the Second Law of Thermodynamics? - Mucesh, Sunil; Chowdhury, Mohammad Nahid; Nutting, Darren; Watters, Daniel (Physics Special Topics, 2016)
The future merger of supermassive black holes residing in the centre of the Milky Way and Andromeda is investigated. Using the Bekenstein-Hawking formula, it is found that the second law of thermodynamics is not violated as the entropy of the system increases by 4.8%.